Effects of castration and sterilization on baseline and response levels of cortisol—A case study in male guinea pigs - Kaiser, Sylvia; Korte, Annika; Wistuba, Joachim; Baldy, Maximilian; Wissmann, Andreas; Dubičanac, Marko; Richter, S. Helene; Sachser, Norbert (Frontiers in Veterinary Science, 2023)
An uncontrolled reproduction of animals in human hands should be avoided. To meet this goal, animals are widely castrated, i.e. the gonads are completely removed. Since the gonads are the most important source of sex hormones, this is a serious intervention in the entire endocrine system of an organism. Sterilization is a much less invasive procedure. Thus, it could have advantages over castration. Therefore, the overall aim of this study was to analyze the effect of castration versus sterilization on the release of glucocorticoids, i.e. an important indicator for welfare. Taking domestic guinea pigs as a model system, we studied baseline and response cortisol values (cortisol is the main glucocorticoid in guinea pigs) in castrated, sterilized, sham-operated and intact males and baseline values in their cohoused females. Whereas baseline values of males did not differ between the groups, castrated males showed significantly higher cortisol response levels than intact, sham-operated and sterilized males. Females housed with castrated, sterilized, sham-operated or intact males did not differ in their cortisol concentrations, neither shortly after being placed with the respective male or after being co-housed for several weeks. Overall, the results support the hypothesis that castrated males exhibited a higher cortisol responsiveness during acute challenge which could point to a generalized impaired welfare of castrated males in comparison to intact, sham-operated and sterilized males. Thus, these results strongly encourage further investigations whether sterilization is not often an alternative to castration in terms of animal welfare.